Public hygiene and funeral rituals during the Risorgimento: mummies and ashes. Issue 4 (13th February 2020) - Marinozzi, Silvia; Messineo, Daniela; Gazzaniga, Valentina; Iorio, Silvia
Abstract : Starting in 1865, regulations pursuant to public hygiene issued by the Unitary Government provided for administrative and political control of the funerary practice. Specifically, they regulated the management of cemeteries and the burials, increasingly drawing the funeral rituals from the control of the Church and of Catholicism, therefore secularising death for the construction of a new political religion. Hygiene became fundamental in order to promulgate cremation as a system of preserving the integrity of the bodies, preserving the ashes as a tangible and indestructible product of body matter and as a measure to protect public health by eliminating the risk of miasmatic pollution of the air caused by the cadaveric fumes. In the early 1870s, the practice of cremation began to spread, especially in the territories of Lombardy-Veneto and Savoy, as an expression of the progressive policies of the new Italian state, antagonistic to the old Catholic religious traditions. This paper intends to highlight the key aspects of the political significance that the cremation took on during the Risorgimento period, while also illustrating the methods adopted by important authors from that time period regarding incineration techniques and cremation methods.